Effect of Work Climate on Labor Fatigue in Kediri Tofu Factory in 2021 - Fahma Tanzila Lahudin; Rachmaniyah Rachmaniyah; Khambali Khambali; Rusmiati Rusmiati; Sahabat Sutanto; Aini Ahmad (International Journal of Advanced Health Science and Technology, 2022)
This study aims to determine the effect of work climate on worker fatigue in Pabrik Tahu Kediri. This research is an observational study with a cross sectional approach. Data was collected by observation, interviews and measurements. The population in the study was 40 workers. The retrieval technique used is Ordinal Regression. The data obtained will be analyzed using the Ordinal Regression test. The variables in this study were labor fatigue as the dependent variable and hot work climate as the independent variable. From the statistical analysis, work fatigue is influenced by the characteristics of the workforce, namely age and gender (p 0.05). The results of the measurement of fatigue before work show that all workers experience low fatigue and 22.2% fatigue after work, 33.3% of workers who experience moderate fatigue and 44.4% of workers who experience high fatigue. The results of the measurement of the working climate in the production room are on average 32°C, which means it exceeds the NAV. Statistical test results show that there is a significant effect of work climate on labor fatigue at 0.001 0.05. Excessive hot work climate can cause body temperature to increase, sweating, which causes the body to lose fluids, salt and cause fatigue. Factors that influence labor fatigue are age, gender, and work climate. Based on the results of this study, the industry is advised to provide drinking places, adding ventilation to reduce heat exposure.